Helsen, Gilis, and Weston (2006) do not err in questioning the optical error hypothesis as the only major account for explaining offside decision-making errors - Helsen, W. F.; Gilis, B.; Weston, M. (Journal of Sports Sciences, 2006)
Oudejans, Bakker, and Beek (2007) recognize several relevant aspects of offside judgements in association football in the paper by Helsen, Gilis, and Weston (2006). We agree that the existing knowledge base on offside assessment needs to be expanded for two reasons. First, from a theoretical point of view it is important to examine how assistant referees can learn to deal with the limitations of the human visual information processing system. Second, from a practical point of view it is relevant to understand better refereeing performances and to identify potential explanations for incorrect offside decisions that could impact on the final outcome of the game. Oudejans et al. (2007) believe we both misinterpreted the optical error hypothesis and that our data set was unsuited to test it. Below, we react to these comments.